ОСОБЛИВОСТІ РЕАЛІЗАЦІЇ ФУНКЦІЇ ПЕРЕТВОРЕННЯ ТРАНСФОРМАТОРНО-КЛЮЧОВОЇ ВИКОНАВЧОЇ СТРУКТУРИ РЕГУЛЯТОРА-СТАБІЛІЗАТОРА НАПРУГИ ЗМІННОГО СТРУМУ - Липківський, К.О.; Можаровський, А.Г. (Інститут електродинаміки НАН України, Київ, 2017)
Devices of the converter equipment with transformer-and-switches executive structures (TSES) intended for implementation of dual types of purposeful changes in the magnitude of the input voltage U1, regulation and stabilization of the output voltage U2 at any required level. To facilitate the analysis of the processes occurring at the same time, it was introduced the definition of a zone on the U1U2 plane as "conversion field", within which there is a plurality of operating points of the converter. The aim of this work is to determine the characteristics of the formation of the conversion field and an array of transfer coefficients of the AC voltage discrete converter. It was proposed to consider the conversion field as a set of cells, in each of which the transformer-and-switches executive structure acts as a conventional two-winding transforming element with inherent voltage transmission coefficient. The problem has been solved in a general form in all ranges of the stabilization and regulation. Dependencies of the number of transfer coefficients and their values from the parameters of the conversion field and the allowable error of the desired voltage value have been determined. Examples of options for the reconfiguration of the conversion field have been presented. References 10, figures 5.